Magnesiothermic Reduction Process Applied to the Powder Production of U(Mo) Fissile Particles. Issue 4 (19th September 2012) - Champion, Guillaume; Allenou, Jérôme; Pasturel, Mathieu; Noël, Henri; Charollais, François; Anselmet, Marie‐Christine; Iltis, Xavière; Tougait, Olivier
Abstract Uranium‐molybdenum alloy powders are obtained by a new synthetic route deriving from the Kroll process which avoids a "melting‐solidification" step. This alternative process consists in the reduction of uranium dioxide by magnesium in presence of Mo in a sealed Mo crucible heated at temperatures ranging from 750 to 1100 °C for dwell periods ranging from 12 to 48 h. An appropriate quenching allows the retention of the high temperature bcc‐form γ–U(Mo). The side products are easily removed by a soaking into a diluted hydrochloric acid solution under sonication. The agglomerates have a typical size in the range 10–200 µm, with an irregular shape. They display even at the periphery equiaxed grains with homogeneous distribution of Mo. Small closed porosity, which seems to be preferentially located at the grain boundaries corresponds to roughly 2% of the volume fraction.